(untitled) (Indian Journal of Child Health, 2022)
A double-chambered right ventricle (DCRV) is a rare congenital heart disease and an uncommon cause of congestive cardiac failure. An anomalous muscle band divides the right ventricle into two cavities, the proximal high-pressure chamber, and distal low-pressurechamber. Its origin is debated. Most cases are diagnosed and treated during childhood. Furthermore, there is tendency for progression, if not treated. Echocardiography is considered useful for diagnosis. About 80–90% patients have associated congenital anomalies, such as ventricular septal defect, pulmonary stenosis, and subaortic stenosis. Isolated DCRV is exceptionally rare. Hence, we are reporting a case of an isolated DCRV in an asymptomatic young female patient.